Domestic service in post-apartheid South Africa : deference and disdain - King, Alison Jill (Ashgate Pub. Co., 2007)
Set within the context of post-apartheid South Africa, the author examines the lives of women in domestic service to discover whether the dismantling of apartheid has ameliorated the poor pay and conditions of this marginalized workforce.